Computational design of core–shell tri-metallic Pd13−nNin@Pt42 (n = 0, 1, 12, and 13) nanoparticles for H2O adsorption and dissociation. (6th July 2017) - Sha, Li; Huang, Shiping
Abstract: Density functional theory calculations are performed to investigate H2 O adsorption and dissociation properties on the icosahedral Pd13 − n Nin @Pt42 (n = 0, 1, 12, and 13) tri-metallic core-shell nanoparticles. The adsorption of H2 O adsorption on the vertex sites of Pd13 − n Nin @Pt42 (n = 0, 1, 12, and 13) nanoparticles, while the adsorption of OH on the bridge site (B1) is preferred, and H is easily absorbed on the vertex and bridge sites. In addition, the reaction pathways of H2 O dissociation on the top of vertex atom (V1) and top of the edge atom (V2) sites of Pd13 − n Nin @Pt42 (n = 0, 1, and 12) nanoparticles, and V1 of the Ni13 @Pt42 are analyzed to explore the H2 O dissociation machanisms. It is found that the addition of Ni atoms in the core of the Pd13 @Pt42 is unbeneficial for the breakage of the OH bond for H2 O dissociation on the Pd13 − n Nin @Pt42 (n = 1 and 12) except Ni13 @Pt42 nanoparticle. Moreover, for the Pd13 − n Nin @Pt42 (n = 0, 1, 12, and13) nanoparticles catalysts, the activity of H2 O dissociation reaction follows the order of Ni13 @Pt42 > Pd13 @Pt42 > Pd12 Ni1 @Pt42 > Pd1 Ni12 @Pt42, illustrating that the Ni13 @Pt42 is the strongest activity among of the Pd13 − n Nin @Pt42 (n = 0, 1, 12, and13) nanoparticles catalysts. Therefore, tuning the composition of Pd and Ni in the core of the Pd13 − n Nin @Pt42 nanoparticles catalysts, the activity of Pd13 − n Nin @Pt42 (n = 0, 1, 12, and 13) nanoparticles catalysts can be modulated effectively. Graphical abstract: Highlights: H2 O adsorption and dissociation on Pd13 − n Nin @Pt42 nanoparticles are investigated. Adding Ni atoms in the core of the Pd13 @Pt42 is unbeneficial for H2 O dissociation. Linear coefficient between adsorption energy of OH and d -band center of Pt is 0.99. Ni13 @Pt42 is the most active catalyst for H2 O dissociation among Pd13 − n Nin @Pt42 NPs.